Isolation and presumptive identification of the major fungi associated with infestation of the Final Year Project Laboratory / Roslinah Mohamad Hussain, Anis Athirah Misri, Siti Rahmah Yusoff - Mohamad Hussain, Roslinah; Misri, Anis Athirah; Yusoff, Siti Rahmah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
In 2017, severe fungal infestation occurred in an adjoining room in the Final Year Project Laboratory at FSK 1,5 UiTM, Puncak Alam. Abundant fungal growth was apparent on walls, ceilings, floor and even furniture. This project aimed to isolate and characterize the major contaminating fungi at the site. Fungal isolation was performed by swabbing the area of infestation using sterile cotton swab and directly spreading onto Sabouraud Dextrose agar, and then subcultured for pure colony growth. Macroscopic (phenotypic) characterization was performed by viewing colony characteristics under 10x and 40x magnifications using the light microscope. Microscopic characterization was performed by tease mount and slide culture methods. Based on macroscopic and microscopic observations of colony morphology characteristics, reproductive structures and growth rate on SDA plate, the two major types of fungi isolated were presumptively identified as Aspergillus spp. and Rhizopus spp.